Relativistic diffusion model with nonlinear drift - Forndran, Frerik; Wolschin, Georg (The European physical journal. A, Hadrons and nuclei, 2017)
.The nonequilibrium-statistical Relativistic Diffusion Model (RDM) is extended to include a nonlinear drift term such that its stationary solution agrees exactly with the thermal equilibrium distribution. The underlying Fokker-Planck equation cannot be solved analytically in this case and we present a numerical solution in rapidity space. The difference to the analytical RDM solution is discussed, and the numerical result is compared to data for net-proton rapidity distributions in sNN−−−−√=17.3sNN=17.3\sqrt{s_{NN}} = 17.3 GeV PbPb and 200 GeV AuAu collisions.
Gesehen am 29.11.2017